PEMBUATAN DAN KARAKTERISASI KARBON AKTIF MONOLIT DARI KAYU KARET DENGAN VARIASI KONSENTRASI KOH UNTUK APLIKASI SUPERKAPASITOR - Inrizky Domy Muchammadsam; Erman Taer; Rakhmawati Farma (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Development of monolithic carbon electrodes with a combination of physical and chemical activation  process  can improve  performance of cell supercapacitor.  Monolithic carbon electrodes  were made  from  rubber wood cross-section of the printed form of  pellets, then  were carbonized  at temperature of  600ºC in N2  gas  atmosphere and  followed by physical activation process at 900ºC  for 2 hours in a CO2  gas atmosphere. KOH of  1 and 5 M  and  HNO3  of  25% solutions  were used as  of the chemical activation  in order  to  activate functional groups. Characterization of electrochemical supercapacitor cell utilized  two-electrode  of  cyclic voltammetry with  1 M H2SO4  solution was used as  electrolyte.  Scanning electron microscope and X-ray diffraction were carried out to study  the structure of surface morphology  and  crystalline properties of monolithic carbon electrodes.  Specific  capacitance  for electrodes  1 M KOH and 5 M KOH  was obtained  as high as  71.08 and 115.38 F/g  respectively.  These results indicate that increasing the concentration of KOH can improve the performance of the electrode supercapacitor cells.